UPAYA GURU DALAM MEMBANGUN INTERAKSI SISWA MELALUI METODE BELAJAR SAMBIL BERMAIN [TEACHER'S EFFORTS IN BUILDING STUDENT INTERACTION USING A GAME BASED LEARNING METHOD] - Rosarian, Ananda Wini; Dirgantoro, Kurnia Putri Sepdikasari (Universitas Pelita Harapan, 2020)
Interaction that occurs in the classroom involves interaction between the teacher and students as well as students and students. One form of class interaction is communication. Communication that is continuously intertwined can also form relationships. A comfortable and pleasant classroom atmosphere is a hope for all class members so that learning objectives can be achieved and can form the class as a shalom community. During the practicum, the writer found that there was no interaction between grade 10 science-track students due to students' individualist attitudes. The teacher as an artist strives and plays a role in creating a pleasant classroom atmosphere through innovative learning methods. Therefore, the writing of this writing aims to find out if the method of learning while playing can build student interaction. The method of learning while playing is one of the innovative, creative, and beneficial learning methods used to increase student interaction and support the achievement of learning objectives. Based on the results of a survey of grade 10 science-track students and mentor feedback, the method of learning while playing using the